PEACEKEEPING DIPLOMACY: PAKISTAN – INDONESIA - Fika Nurislamia (Universitas Jenderal Ahmad Yani, 2023)
The United Nations Security Council Resolution 1325 on Women, Peace and Security (WPS Agenda) adopted in 2000 is a global milestone that centers women's issues in peace and security efforts. It recognizes the terrible impacts of conflict on women. The WPS Agenda has prompted a call for all UN member states to enhance the participation of women in conflict prevention and resolution as an effort to realize sustainable peace, including by increasing the number of female peacekeepers in the UN Peacekeeping Operations (UN PKO). This research uses a qualitative method by employing a library research approach. It examines relevant foreign policy documents of both countries pertaining to the WPS Agenda and engaging with existing scholarships on the WPS Agenda. Informed by constructivist international relations theory focusing on state norms and identities, this research argues that the Pakistani government's commitment to incorporate a gender perspective in UN peace and security efforts is shaped by the political will of the military government. It has resulted in the recognition of Pakistan in international forums. The increased female peacekeepers in UN operations become an effective tool for peacekeeping diplomacy of both countries so that they could influence the UN global decision-making process.